Cognition, functionality, and life space in older adults: the mediating role of perceived control and autonomy - Eduardo Amorim Rocha; Anita Liberalesso Neri; Monica Sanches Yassuda; Samila Sathler Tavares Batistoni (Brazilian Society of Geriatrics and Gerontology, 2023)
Objectives: To examine a model of associations between cognition, functionality, and life-space mobility, and the mediating role of perceived control and autonomy. Methods: This is a cross-sectional study with a sample of older adults aged over 72 years, which used data from the FIBRA study. We used the structural equation modeling technique. Variables in this model were cognition, functionality, perceived control and autonomy, and life-space mobility, with sociodemographic and health covariables. Data imputation was done through the expected maximization method aiming at more effective data utilization. This study was funded by Coordenaçãão de Aperfeiçoamento de Pessoal de Nível Superior. Results: The mediation model reached good fit indices. Cognition, functionality, and perceived control and autonomy demonstrated a predictive capacity for life space. Functionality and perceived control and autonomy mediated the relationship between cognition and life space; therefore, cognition influences life space, given its associations with the mediating variables. There was a mediating effect of perceived control and autonomy on the relationship between functionality and life space. Conclusions: Perceived control and autonomy have an adaptive role when considering changes in personal competencies. This adaptation is reflected on life spaces, indicating an adjustment between competence and environment. Studies aimed at promoting a good relationship between an individual and his or her context maintaining life space should consider perceived control and autonomy as important mechanisms in this relationship.